Kajian Semiotika pada Adegan Film “The Architecture of Love”: Studi Kasus Adegan Trauma Karakter River - Mega Rahmatika Putri; Rahmat Wisudawanto; Dyah Retno Pratiwi (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
This study examines the presentation of trauma in the character of River in the film “The Architecture Of Love” through Roland Barthes' semiotic analysis, which includes three levels of meaning: denotative, connotative, and mythological. The focus of this study is on scenes that reflect trauma, categorized according to Cavanagh.M. (1982) theory as situational, developmental, intrapsychic, and existential trauma. The methodology used is descriptive-qualitative with documentation and observation techniques, where all trauma scenes are identified and analyzed in depth. The results of the study show that intrapsychic trauma is the dominant category, followed by existential, situational, and developmental trauma. The representation of trauma in the character River is conveyed through visual symbols such as dark colors, a closed language system, dim lighting, and a quiet urban atmosphere, which create emotional meaning without verbal expression. This finding confirms that films can convey complex psychological experiences through visually rich language, while also revealing new insights into non-verbal communication in film media.